2020
DOI: 10.1109/access.2020.3030339
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Intimacy Based Positive Emotions Contagion Peer Public Safety Evacuation Behavior

Abstract: Behavioral simulation plays an important role in many scenarios, such as emergency evacuation and public safety. The importance of public security in modern life can be seen in the epidemic outbreak in 2020. In particular, the epidemic can affect people's psychology and emotions and change people's behavior. Therefore, how to effectively improve people's positive emotions in a panic has become an urgent problem. In social relations, most behaviors are produced by peer interaction. To simulate the interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Based on the reviewed papers, validation of models of emotion contagion currently is not approached in a uniform way. One form of content validation that was used in five studies simulating emergency situations [53,61,65,70,87] is that of face validity. Typically, these authors showed the visual output of simulations and video of real incidents to people, or let people interact with the model in the form of a serious game.…”
Section: Validation and Empirical Datamentioning
confidence: 99%
“…Based on the reviewed papers, validation of models of emotion contagion currently is not approached in a uniform way. One form of content validation that was used in five studies simulating emergency situations [53,61,65,70,87] is that of face validity. Typically, these authors showed the visual output of simulations and video of real incidents to people, or let people interact with the model in the form of a serious game.…”
Section: Validation and Empirical Datamentioning
confidence: 99%